The Influence of Work Environment, Management Support, Organizational Culture, and Employee Engagement on Employee Performance Through Employee Satisfaction - Maulia Farah Nur Azizah; Bambang Widjanarko Otok (Publikasi Indonesia, 2024)
In an era of globalization, companies must optimize their resources to meet customer needs. To improve the quality of human resources, companies must focus on areas such as the work environment, management support, organizational culture, employee engagement, and employee satisfaction. The study aims to identify the employee's performance in relation to its association with the variable studied and analyze it based on the supporting component. Data collection occurs through surveys and questionnaires, while analysis methods include Structural Equation Modeling (SEM). The results showed that a significant relationship between employee performance and employee characteristics on the work environment variable of 0.473 and employer engagement of 0.440 has been demonstrated. Employees who work in a positive and supportive work environment and feel engaged in their work tend to be more committed, more productive and qualified, more satisfied and motivated, and have a positive work culture. These aspects have the ability to increase employee satisfaction and employee performance, which in turn contribute to the overall success of the company.